Clinical characteristics and treatment choice in vestibular migraine. (June 2018) - Power, L.; Shute, W.; McOwan, B.; Murray, K.; Szmulewicz, D.
Highlights: Vertigo (96%) and headache (60%) were the predominate symptoms. Headache not a necessary symptom of vestibular migraine. 86% of patients had a normal exam. Six (5%) had a positive vHIT and seven (6%) had oculomotor abnormalities. Pizotifen (30%) and amitriptyline (21%) were the two most commonly used medications. On average 1.4 different medications were required to obtain symptom control. Only 16% were referred for physiotherapy, despite 56% reporting motion-induced symptoms. Physiotherapy is underutilised. Abstract: This retrospective review aims to survey the clinical characteristics and management of vestibular migraine (VM) patients seen in a tertiary hospital multi-disciplinary balance disorders clinic, and how this aligns with the evidence base in the literature. A single investigator reviewed the medical records of the patients who presented to a tertiary hospital balance disorders clinic over a four month period and identified 90 cases of VM. The mean age of patients with a diagnosis of VM was 50 years (range of 17–84) and 72 (80%) were female. Vertigo (96%) and headache (60%) were the predominate symptoms. Vestibular function testing abnormalities included six (5%) with a positive video head impulse test and seven (6%) with oculomotor abnormalities. Pizotifen (30%) and amitriptyline (21%) were the two most commonly used medications whilst only 14 (16%) received vestibular physiotherapy. This study suggests that VM is a very common presentation to a tertiary balance disorders clinic, but there is little consensus in choice of initial management and vestibular rehabilitation is underutilized. This data may be valuable in informing the practice of neuro-otology as well as in the planning of future service provision.